The efficacy of atorvastatin on inflammation and coagulation markers in high-risk thrombotic cancer patients undergoing chemotherapy: a randomized controlled trial - Budi Setiawan; Widi Budianto; Tri Wahyu Sukarnowati; Daniel Rizky; Eko Adhi Pangarsa; Damai Santosa; Aru Wisaksono Sudoyo; Tri Indah Winarni; Ignatius Riwanto; Rahajuningsih Dharma Setiabudy; Catharina Suharti (Thrombosis Journal)
Abstract Background Deep vein thrombosis (DVT) is a prevalent complication associated with malignancy. Clinical use of thromboprophylaxis is recommended, however its usage is limited due to bleeding complications, more cost associated, and reluctance to receive anticoagulant injections. Rivaroxaban a relatively easy to administer anticoagulant but it has a risk of bleeding and is expensive. Inflammation is the important factor in pathogenesis of cancer-associated thrombosis. Statins have the anti-inflammatory property that could decrease proinflammatory cytokines. Consequently, statins may be used as thromboprophylaxis for cancer patients receiving chemotherapy. Objective To provide comparison between atorvastatin and rivaroxaban on affecting inflammatory biomarkers (interleukin 6 [IL-6], C reactive protein [CRP]) and coagulation activation biomarkers (Tissue Factor [TF], prothrombin fragment 1 + 2 [F1 + 2], D-Dimer) in cancer patients at high risk of thrombosis receiving chemotherapy. Methods A randomized controlled study that was double-blinded and involved high-risk cancer patients undergoing chemotherapy. For up to ninety days, participants were randomized to receiver either atorvastatin 20 mg or rivaroxaban 10 mg daily. The level of plasma of IL-6, CRP, TF, F1 + 2, and D-dimer were assessed 24 h before chemotherapy, 30, 60, and 90 day after chemotherapy. The latest observation carried forward (LOCF) approach was used to examine the data. The laboratory results were evaluated using an independent T test or Mann-Whitney U test prior to and after chemotherapy. Results Eighty-six randomized patients were enrolled, although both groups showed a decreasing trend in plasma level of IL-6, CRP, TF, F1 + 2, and D-dimer, there were no significant differences between the two groups (p > 0.05). In the atorvastatin group, there was a significant correlation between delta level of IL-6 and F1 + 2 (r = 0.313, p = 0.043) and delta level of CRP and F1 + 2 (r = 0.398, p = 0.009), whereas in the rivaroxaban group there was a significant correlation between delta CRP and D-dimer level (r = 0.387, p = 0.009). Conclusion Atorvastatin decreases IL-6 and CRP level, which also decreases F1 + 2 level. Atorvastatin did not substantially differ from rivaroxaban in decreasing plasma levels of inflammatory biomarkers IL-6, CRP, and coagulation activation biomarkers TF, F1 + 2, D-dimer in high-risk cancer patients undergoing chemotherapy. Trial registration ISRCTN71891829, Registration Date: 17/12/2020.